PENGARUH KOMBINASI BUDESONIDE DAN FORMOTEROL TERHADAP KEKASARAN PERMUKAAN RESIN KOMPOSIT BIOAKTIF - Alya Rahmasari; Isyana Erlita; Sherli Diana (Dentin, 2021)
ABSTRACT      Background: The combination of budesonide and formoterol is an effective treatment for asthma. The fumaric acid contained in the combination asthma drug budesonide and formoterol affects the condition of the oral cavity, so that it becomes acidic and causes surface roughness of tooth restorations, one of which is a composite resin whose physical properties and materials have been developed, namely bioactive composite resin. Objective: To know the effect of exposure to the combination of budesonide and formoterol asthma drug 320/9µg, 640/18µg, which was soaked only in artificial saliva on the surface roughness of the composite resin. Method: This study use a sample in the form of a disc-shaped bioactive composite resin, 10mm in diameter and 2mm in thickness using ISO 4049 specifications and divided into 3 groups, namely the group exposed to the combine asthma drug budesonide and formoterol at doses of 320/9µg, 640/18µg, and the group that was immersed in artificial saliva. Result: One Way ANOVA and Post Hoc Bonferonni showed a significant difference in the roughness value of the bioactive composite resin between group exposed to the combination of budesonide and formoterol asthma drug 640/18µg and the group that was soaked only in artificial saliva. Conclusion: There is an effect of exposure to the combination of budesonide and formoterol asthma drug on the surface roughness of the bioactive composite resin. Keywords: bioactive composite resin, budesonide and formoterol, surface roughness. ABSTRAK      Latar Belakang: Kombinasi budesonide dan formoterol merupakan penanganan yang efektif untuk mengatasi asma. Asam fumarat yang terkandung dalam obat asma kombinasi budesonide dan formoterol mempengaruhi kondisi rongga mulut, sehingga menjadi asam dan menyebabkan kekasaran permukaan restorasi gigi yang salah satunya adalah resin komposit yang telah dikembangkan sifat fisik dan materialnya yaitu resin komposit bioaktif. Tujuan: Untuk mengetahui pengaruh paparan obat asma kombinasi budesonide dan formoterol 320/9µg, 640/18µg, dan hanya direndam saliva buatan terhadap kekasaran permukaan resin komposit. Metode: Penelitian ini menggunakan sampel berupa resin komposit bioaktif yang berbentuk cakram berdiameter 10mm dan tebal 2mm menggunakan spesifikasi ISO 4049 serta dibagi menjadi 3 kelompok yaitu kelompok paparan obat asma kombinasi budesonide dan formoterol 320/9µg, 640/18µg dan yang hanya direndam saliva buatan. Hasil: One Way ANOVA dan Post Hoc Bonferonni menunjukkan perbedaan bermakna pada nilai kekasaran resin komposit bioaktif antara kelompok paparan obat asma kombinasi budesonide dan formoterol 640/18µg dengan kelompok yang hanya direndam saliva buatan. Kesimpulan: Terdapat pengaruh paparan obat asma kombinasi budesonide dan formoterol terhadap kekasaran permukaan resin komposit bioaktif. Kata kunci: Budesonide dan formoterol,kekasaran permukaan, resin komposit bioaktif.